Hydrogen bond acceptors and additional cationic charges in methylene blue derivatives: photophysics and antimicrobial efficiency. - Felgenträger, Ariane; Maisch, Tim; Dobler, Daniel; Späth, Andreas (BioMed Research International, 2013)
Photodynamic inactivation of bacteria (PIB) by efficient singlet oxygen photosensitizers might be a beneficial alternative to antibiotics in the struggle against multiresistant bacteria. Phenothiazinium dyes belong to the most prominent classes of such sensitizers due to their intense absorption in the red-light region (¿(abs, max) ca. 600-680¿nm, ¿ > 50,000¿L¿mol(-1)¿cm(-1)), their low toxicity, and their attachment/penetration abilities. Except simple substituents like alkyl or hydroxyalkyl residues, nearly no modifications of the phenothiaziniums have been pursued at the auxochromic sites. By this, the properties of methylene blue derivatives and their fields of application are limited; it remains unclear if their potential antimicrobial efficacy may be enhanced, also to compete with porphyrins. We prepared a set of six mainly novel methylene blue derivatives with the ability of additional hydrogen bonding and/or additional cationic charges to study the substituents' effect on their activity/toxicity profiles and photophysical properties. Direct detection of singlet oxygen was performed at 1270¿nm and the singlet oxygen quantum yields were determined. In suspensions with both, gram-positive and gram-negative bacteria, some derivatives were highly active upon illumination to inactivate S. aureus and E. coli up to 7 log10 steps (99.99999%) without inherent toxicities in the nonirradiated state.